IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT IN ACHIEVING SCHOOL QUALITY - Rama Aditya Pratama; Rama Meiagriza; Sulis Anggraeni; Aslamiah; Celia Cinantya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe the implementation of continuous development, based on the Plan-Do-Check-Act (PDCA) cycle, at SDN Abirau, Banjar Regency, to enhance school quality holistically. A descriptive qualitative approach was employed, utilizing data collection techniques such as in-depth interviews, participatory observation, and documentation analysis involving the principal, teachers, and educational staff. Data analysis followed Miles and Huberman's interactive model, with source and method triangulation used to ensure data validity. The findings indicate that SDN Abirau has implemented end-of-semester reflections, teacher professional training, communities of practice, learning outcome evaluations, and the PDCA cycle in its quality management. Supporting factors include visionary leadership, a strong teacher community, and a reflective culture. Conversely, the main obstacles are time constraints, incomplete documentation, mismatched training materials, and uneven teacher participation. The study's novelty lies in the integration of comprehensive stakeholder involvement and the utilization of real-time data within the elementary school context. Practical recommendations include strengthening the training needs analysis, improving PDCA documentation, increasing the frequency of teacher communities, enhancing participation in evaluations, and fostering a continuous improvement culture supported by adequate resources. Consequently, continuous development serves as an effective strategy for improving school quality systematically and sustainably